Differences in rate and medical indication of caesarean section between Germany and Japan. Issue 9 (30th September 2020) - Fröhlich, Matthias; Koga, Chie; Bührer, Christoph; Mori, Chisato; Yamamoto, Midori; Sakurai, Kenichi; Hinkson, Larry; ,
Abstract: Background: There are growing concerns about the increasing rate of caesarean section (CS) worldwide. Various strategies have been implemented to reduce the proportion of CS to a reasonable level. Most research on medical indications for CS focuses on nationwide evaluations. Comparative research between different countries is sparse. The aim of this study was to evaluate differences in the rate and indications for CS between Japan and Germany in 2012 and 2013. Methods: Comparison of the overall rate and medical indications for CS in two cohort studies from Germany and Japan. We used data from the German Perinatal Survey and the Japan Environment and Children's Study (JECS). Results: We analyzed data of 1 335 150 participants from the German perinatal survey and of 62 533 participants from JECS and found significant differences between the two countries in CS rate (30.6% vs 20.6%) and main medical indications: cephalopelvic disproportion (3.2% vs 1.3%; OR: 2.4 [95% CI: 2.2–2.6]), fetal distress (7.3% vs 2.3%; OR: 3.4 [95%‐CI: 3.2–3.6]), and past uterine surgery/repeat CS (8.4% vs 8.8%; OR: 0.9 [95%‐CI: 0.9–1]). Conclusion: There are differences in the rate and medical indications for CS between Germany and Japan at the population level. Fetal distress was identified as a medical indication for CS more often Germany than in Japan. Considering the substantial diagnostic uncertainty of electronic fetal monitoring (EFM) as the major indicator for fetal distress, it would seem to be reasonable to rethink CS decision algorithms.